Is there still a West? : the future of the Atlantic Alliance - Hay, William Anthony, 1968-; Sicherman, Harvey (University of Missouri Press, 2007)
"Scholarly essay collection that considers whether "the West" is still a major force in international affairs or whether we face a new world of competing states and shifting alliances. In proposing possible counterterrorism strategies to define a shared Western security policy, they offer an alternative to neoconservative and liberal viewpoints"--Provided by publisher